Mucosa and rejection in facial vascularized composite allotransplantation: a systematic review - Kauke-Navarro, Martin; Safi, Ali-Farid; Zhegibe, Ana; Haug, Valentin; Kollár, Branislav; Nelms, Laurel; Palmer, William Jackson; Tchiloemba, Bianief; Lian, Christine G.; Murphy, George F.; Pomahac, Bohdan (Transplantation, 2020)
Background. - Facial vascularized composite allotransplantation (fVCA) presents an established approach to restore form and function of patients with catastrophic facial defects. Skin is one of the target tissues of the rejection process, and due to its easy accessibility has become the gold standard in the diagnosis of rejection. Mucosal rejection frequently occurs; however, the added value of mucosal rejection assessment for patient management is unknown. - Methods. - We conducted a systematic review of manuscripts listed in the MEDLINE/PubMed and GoogleScholar databases to identify articles that provide data on mucosal rejection following fVCA. For inclusion, papers had to be available as full-text and written in English. Non-VCA studies and animal studies were excluded. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. - Results. -We included 17 articles that described changes in allotransplanted mucosa of fVCAs. These articles yielded data on 168 BANFF graded biopsies of corresponding skin and mucosa biopsies. Rejection grades were consistently higher in mucosal biopsies. Concordance between allograft skin and mucosa biopsy grades increased with an increasing skin-BANFF grade. Mucosa rejection grades were on average lower in the early stages of the posttransplant period (<postoperative mo 12, time of motor, and sensory recovery) when compared to the later stages (>postoperative mo 12). - Conclusions. - The mucosa of facial allotransplants is one of the primary targets of rejection. The data indicates that higher-grade skin rejection does not occur in absence of mucosal rejection. Further investigations are needed to elucidate the exact role of mucosal biopsies for fVCA patient management.